2016
DOI: 10.1038/ncomms11360
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pyrazolopyridazinones as PDEδ inhibitors

Abstract: The prenyl-binding protein PDEδ is crucial for the plasma membrane localization of prenylated Ras. Recently, we have reported that the small-molecule Deltarasin binds to the prenyl-binding pocket of PDEδ, and impairs Ras enrichment at the plasma membrane, thereby affecting the proliferation of KRas-dependent human pancreatic ductal adenocarcinoma cell lines. Here, using structure-based compound design, we have now identified pyrazolopyridazinones as a novel, unrelated chemotype that binds to the prenyl-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 23 publications
(48 reference statements)
6
162
0
Order By: Relevance
“…Depletion of PDEδ results in RAS mis-localization and consequently in attenuated signaling. Earlier deltarasin and recently deltazinone 1, which shows relatively less nonspecific cytotoxicity than deltarasin, were developed as inhibitors of the KRAS4b-PDEδ interaction (Papke et al, 2016; Zimmermann et al, 2013). …”
Section: Ras Proteins In the Membranementioning
confidence: 99%
“…Depletion of PDEδ results in RAS mis-localization and consequently in attenuated signaling. Earlier deltarasin and recently deltazinone 1, which shows relatively less nonspecific cytotoxicity than deltarasin, were developed as inhibitors of the KRAS4b-PDEδ interaction (Papke et al, 2016; Zimmermann et al, 2013). …”
Section: Ras Proteins In the Membranementioning
confidence: 99%
“…This suggests that Deltarasin eventually modulates several off-targets and so the 'switch-like' behavior in growth inhibition assays may be due to general cytotoxicity, rather than dependent on the approach to block the PDEδ/KRas interaction. Indeed, Deltazinone 1 inhibited the cell growth of KRas dependent cell lines in a clear dose-dependent manner, and did not show unspecific cytotoxicity even at 24 μm concentrations (Papke et al, 2016). Because Deltazinone 1 needed at least 10 μm concentrations to show an effect in cell-based assays, this limitation may not be chemotype-but systemdependent.…”
Section: Pyrazolopyridazinone Derivativesmentioning
confidence: 99%
“…This prompted us to develop a novel PDEδ inhibitor chemotype to address the question whether those limitations were chemotype-dependent or intrinsic to the PDEδ-inhibition approach. To identify alternative chemotypes, further analysis of the previously developed high-throughput Alpha Screen hit set pointed towards pyrrolopyridazinone 14 and pyrazolopyridazinone 15 as inhibitors of the PDEδ/KRas interaction (Figure 4) (Papke et al, 2016;Murarka et al, 2017).…”
Section: Pyridazinone Inhibitors Targeting Pdeδmentioning
confidence: 99%
“…Structural analysis, showed that these transport proteins provide with a hydrophobic grove suitable to adopt the hydrophobic farnesyl group on the K-Ras protein, thereby increasing its water solubility (26)(27)(28). To test how this process affects the translocation of the protein from the PM to the Golgi, we pretreated cells with deltarasin, a compound that competes to Ras binding by mimicking the structure of farnesyl groups (26).…”
Section: Acute Manipulation Of Pm Ppins Poolsmentioning
confidence: 99%